Ramadan-specific nutrition education improves cardio-metabolic health and inflammation—a prospective nutrition intervention study from Pakistan - Gul, Rahmat; Khan, Imran; Alam, Iftikhar; Almajwal, Ali; Hussain, Imtiaz; Sohail, Namrah; Hussain, Muhammad; Cena, Hellas; Shafiq, Sunara; Aftab, Anam (Frontiers in Nutrition, 2023)
There are recent reports that Ramadan fasting (RF) results in weight gain instead of weight loss. In addition, data on efficacy of brief nutrition education (NE) on healthy eating practices during Ramadan for better health is scarce. Therefore, a prospective observational study was conducted to investigate effects of brief nutrition before the start of RF on healthy eating practices during RF. Study focused on "Dietary Education and Awareness for Ramadan (DEAR)" as an intervention . The participants (n=74) were recruited and divided into two groups i.e. intervention and control groups (n=37 each). As an intervention, (NE) lessons were given before and during RF month to intervention group. Data on anthropometrics, dietary intake and other parameters were collected at three time points. Weight was measured in (kg), height, waist circumference (WC) and hip circumference (HC) were measured in (cm), body mass index (BMI) was calculated. Waist to hip ratio (WHR) was calculated. Body composition analysis were performed by body composition analyzer (BF-907). Blood pressure (BP) was measured by a validated BP monitor. 3-5 ml of venous blood was collected, plasma and serum were separated. Serum and Plasma were processed for general blood chemistry (blood lipid profile, glucose and CRP). Fasting blood glucose was determined. CRP was determined by immuneturbidometry method by auto analyzer. ELISA was used to determine cytokine/chemokines. Adherence to (NE, intervention) was assessed. Results show (NE) had positive effects on overall nutrition. Significant improvement in dietary adherence to dietary advices in the intervention group were noted. Significant BW loss (mean:1.21 Kg) in intervention group was observed. Majority (63.3%) had lost BW ≥ 1.0 kg. Other changes observed as a result of intervention included improvement in blood glucose, cholesterol, CRP levels and BP. There was notable shift in pro-and antiinflammatory cytokines concentrations: IL-7, IL-4 and TGF-α decreased, while IL-2, TNF-α and Resistin, IL-1 RA, IL-17 A, and sCD40 increased. In conclusion, RF resulted in loss in mean BW and improvement in related blood chemistry and cytokines profile. Further, nutrition education before RF resulted in better nutrition practices during RF and brought desirable healthy BW, blood lipid and cytokine profile.